SERVICE QUALITY OF REGIONAL GENERAL HOSPITAL DR. H. MOH. ANWAR SUMENEP DISTRICT - Wardatunnisa Firdaus Azizah; Sri Wibawani (PAJ, 2021)
SERVICE QUALITY OF REGIONAL GENERAL HOSPITAL DR. H. MOH. ANWAR SUMENEP DISTRICT